Using a Transactional Model and Thematic Analysis to Evaluate a Minority Male Student Success Initiative to Improve Participants’ Campus Experience and Retention - Richard Mensah; Kathryn Todd Bliss; Alexis Rodgers; Falynn Thompson; Kelly D. Bradley (International Journal of Assessment Tools in Education)
While the national discourse about the call forincreased effort to help strengthen retention and graduation rates amongminority college students seems to be losing its vigor, concerned citizens continueto find other means to sustain the momentum. Similarly, the office for institutional diversity ata public southeastern university established a minority malestudent success initiativein 2010 to help improve the educational experience of its members. The evaluators’objectives for this transactional,formative, and qualitative evaluationwere to understand this initiative from the different vantage pointsof its stakeholders, and to determine if they were satisfied thus far with its trajectory. The evaluators found that while somestakeholders held similarperspectives, others differedin their views on the initiative’s goal(s). The majority, however, expressedsatisfaction with the initiative'sdirection at the time of the evaluation.